Seasonal Urinary Levels of Glyphosate in Children From Agricultural Communities - Felipe Lozano-Kasten MD, PhD; Erick Sierra-Diaz MD, PhD; Humberto Gonzalez Chavez PhD; Alejandro Aarón Peregrina Lucano PhD; Rosa Cremades; Elena Sandoval Pinto PhD (SAGE Publishing, 2021)
Background Glyphosate is one of the most commonly used pesticides in agricultural activities worldwide. For the last 20 years, its use has increased rapidly becoming a public health concern. The IARC classified glyphosate as probably carcinogenic; however, the reported evidence is not enough to establish a statement. Objective This work aimed to measure glyphosate levels in the urine of children from a single rural community in an endemic region of chronic kidney disease and malnutrition. Methods A cross-sectional study was carried out in a rural community in western Mexico. The study included 95 children between the ages of 6 and 16. A urine sample (first-morning spot) was obtained from children and processed to measure glyphosate levels using high-performance liquid chromatography coupled with tandem mass spectrometry. Results All samples tested positive for glyphosate levels. Urine glyphosate levels were related to the season and the age of the children. Conclusion Glyphosate is present in children of all ages in the community even if they were not in direct contact with it. No toxicity cases were reported, nor were there other health problems related to glyphosate. However, more long-term studies should be done that provide a statement regarding the harmful effects that glyphosate has on public health.